2014
DOI: 10.1021/ol403472y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of trans-2,6-Disubstituted Cyclohexanones through Allylic Substitution

Abstract: trans-2,6-Disubstituted cyclohexanones were synthesized with high regio- and stereoselectivity by allylic substitution followed by ozonolysis. Both alkyl and aryl groups were successfully installed to the cyclohexane ring. The stereochemistry of the SN2' products was determined to be controlled by the pre-existing chirality on the ring. The present method is highlighted by the synthesis of enantiomerically enriched cyclohexanones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[7][8][9] Chelation of the carbonyl oxygen and the pyridyl nitrogen in the picolinoxy moiety to MgBr 2 , produced in situ from…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Chelation of the carbonyl oxygen and the pyridyl nitrogen in the picolinoxy moiety to MgBr 2 , produced in situ from…”
Section: Introductionmentioning
confidence: 99%
“…We found that the necessary allylic silane 10 was accessible via a short sequence from bromoenone 2 (Scheme ). 1,2-Reduction of the ketone under Luche conditions was followed by activation of the resulting allylic alcohol as the corresponding carbonate. Treatment of this intermediate with silyl cuprate reagent resulted in efficient conversion to 10 .…”
mentioning
confidence: 99%